Functional study of Villin 2 protein expressed in longissimus dorsi muscle of Korean native cattle in different growth stages - Yong-Cheng Jin; Jeng-A Han; Cheng-Xiong Xu; Sang-Kee Kang; Sang-Hun Kim; Kang-Suk Seo; Du-Hak Yoon; Yun-Jaie Choi; Hong-Gu Lee (BMB Reports, 2012)
The aim of this study was to investigate protein profiles relatedto the induction of adipogenesis within the bovine longissimusdorsi muscle (BLDM) by proteomic analysis. We analyzedBLDM proteins at different growth stages to clarify the physiologicalmechanisms of marbled muscle development in 20head of Korean native cattle (11 month: 10 head, 17 month: 10head). BLDM proteins were analyzed by two-dimensional electrophoresisand image analysis. Villin 2 was specifically identifiedby mass spectrometry and a protein search engine. Villin 2protein expression in BLDM decreased during the fat developmentstage in test steers. In a Western blot cell culture study ofspontaneously immortal bovine muscle fibroblasts, the abundanceof Villin 2 was shown to be down-regulated during differentiationinto muscle. In 3T3-L1 mouse embryonic fibroblasts,Villin 2 was decreased during differentiation intoadipocytes. The results suggest that Villin 2 may be related tothe induction of transdifferentiation and adipogenesis in bovinelongissimus dorsi muscle. [BMB reports 2012; 45(2): 102-107]